Desempeño docente en instituciones educativas públicas entre participantes y no participantes del programa de capacitación docente en maestría convenio UNE - región Callao - Menacho Ángeles, Vilma Rosario (2010)
Describes levels of educational performance between participants and non participants in the agreement master teacher training provided by the Callao Region, 2006-2008. The sample consisted of 360 students, 06 managers and 72 teachers selected through a process not probabilistic intentional. The methodology was descriptive cross-sectional comparative baseline. The subjects were interviewed and also used an observation form. A comparative level, no difference was found between the groups studied. The appreciation of students as managers also no evidence of significance levels for the groups compared. It is noted that students, the managers and the results of the observation form, consider the performance of their teachers as average.